Advances in Wheat Genetics: From Genome to Field Proceedings of the 12th International Wheat Genetics Symposium - Ogihara, Yasunari; Takumi, Shigeo; Handa, Hirokazu (Springer Nature, 2016)
plant genetics; plant genomics; agriculture